Performance of polyester/epoxy binder coating system – studies on coating resistance, adhesion and differential scanning calorimetry. Issue 3 (3rd May 2016) - Ismail, L.; Ramesh, K.; Mat Nor, N.A.; Jamari, S.K.M.; Vengadaesvaran, B.; Arof, A.K.
Abstract : Purpose: The purpose of this paper is to study the electrochemical, mechanical and thermal characteristics of polyester – epoxy coating systems using electrochemical impedance spectroscopy (EIS), pull-off test and differential scanning calorimetry (DSC). These are very important properties to evaluate the performance of a coating system. Proper measurement and analysis techniques are needed for a proper evaluation of these properties to ensure the coating performance. Design/methodology/approach: Different ratios of polyester and epoxy resins have been blended to formulate good anticorrosive, mechanically strong and thermally stable binder coating system. EIS, pull-off test and DSC were used to evaluate these properties. Findings: The sample containing 90 wt.% polyester exhibited the best corrosion resistance from the beginning until the end of exposure time. The value of corrosion resistance (Rc ) obtained on the 30th day of exposure was found to be 2.89 × 108 ohm cm −2 . The glass transition temperature (Tg ) was found to be increasing with the incorporation of epoxy to the binder system. The result from pull-off test showed the best adhesion with the sample containing 90 wt.% polyester which also has the lowest Tg promoted better adhesion properties. Practical implications: The curing time must be reduced for practical applications. Originality/value: Hybrid coatings systems have been formulated. This paper discusses on the highest coating resistance obtained polymer-substrate mechanical properties and thermal characteristic of the polyester/epoxy binder resin using DSC.